(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical foundations of the socio-philosophical analysis of the factor of art in the process of spiritual upliftment, the socio-philosophical aspects of the possibilities of art in the process of spiritual upliftment, the future tasks of the development of art in the process of spiritual upliftment. Also, the socio-philosophical analysis of the possibilities of art in the process of spiritual upliftment of New Uzbekistan is carried out.